Analisis makna, fungsi dan simbol dalam tuturan hada gene (perkawinan adat) masyarakat Retta di Alor - Ester Dakabesi; Labu Djuli; Samuel Nitbani (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
This study aims to analyze the meanings, functions, and symbolism of traditional utterances in the Tamia Tapuni customary wedding ceremony of the Pulau Pura (Retta) community, Alor Regency. Traditional marriage is not merely understood as the union of two individuals, but also as a social and cultural event that embodies local values, beliefs, and cultural identity. This research focuses on the traditional utterances spoken during each stage of the wedding ceremony and the accompanying symbols, including ritual objects, ceremonial actions, and procedural structures. The research employs a qualitative approach with a descriptive method and adopts an ethnographic type of study. Data were collected through observation, interviews with traditional leaders and community members, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The theoretical framework includes Speech Act Theory, Symbolic Interactionism, Koentjaraningrat’s cultural theory, and Charles Sanders Peirce’s semiotic theory. The findings reveal that traditional utterances in the Tamia Tapuni wedding ceremony contain symbolic, social, and religious meanings and function as a medium for strengthening family relations, legitimizing customary practices, and conveying moral values. The symbols used in the ceremony reflect harmony, respect for ancestors, and the social structure of the Pulau Pura community. This study is expected to contribute to the fields of linguistic anthropology and semiotics and to support the preservation of local cultural traditions amid modernization.